O ACÓRDÃO N.º 298/2019 DO TRIBUNAL CONSTITUCIONAL — UMA (BREVÍSSIMA) ANÁLISE METODONOMOLÓGICA E CRÍTICA: Flávio Serrano Roques (De Legibus - Law Journal, 2021)
This article is a reflection on the various methodological issues raised around Judgment No. 298/2019 of the Portuguese Constitutional Court. In this study, therefore, a methodonomological and critical analysis of a judicialconstitutional decision is made ( Judgment No. 298/2019 of the Portuguese Constitutional Court). Based on the respective grounds, we seek to examine, understand, describe and systematize the path taken by the decision maker- in this case, the judges of the Constitutional Court who signed the judgment -, since the initial confrontation with the problem, the moment of delimitation of the problem, until the final decision, trying to determine, as far as possible, if this decision, in view of the methodical model adopted, appears to be adequate, correct, in short, just.